Horizons(student's book 2) : - Radley, Paul (Oxford University Press, 2005)
This is a four-level secondary course that sets achievable goals. Colin Campbell works as a Lecturer at the Centre for Applied Language Studies, running short courses for overseas teachers of English. He has worked extensively as a teacher, teacher trainer, and project manager in Poland, Estonia, Spain, Italy, the UK, and Ireland.